2013
DOI: 10.1016/j.pneurobio.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple interacting cell death mechanisms in the mediation of excitotoxicity and ischemic brain damage: A challenge for neuroprotection

Abstract: There is currently no approved neuroprotective pharmacotherapy for acute conditions such as stroke and cerebral asphyxia. One of the reasons for this may be the multiplicity of cell death mechanisms, because inhibition of a particular mechanism leaves the brain vulnerable to alternative ones. It is therefore essential to understand the different cell death mechanisms and their interactions. We here review the multiple signaling pathways underlying each of the three main morphological types of cell death--apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
148
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(155 citation statements)
references
References 388 publications
(448 reference statements)
2
148
0
5
Order By: Relevance
“…Several cell-death morphologies have been identified in different regions of the brain after neonatal hypoxic-ischemic injury, but neuron-specific deletion of Atg7 or intracerebroventricular treatment with the autophagy inhibitor, 3-MA, is sufficient to reduce infarct lesion volume, indicating that autophagy may be upstream of multiple death pathways. This supports our previous recommendation that postischemic treatment of neonatal cerebral hypoxia-ischemia should target autophagy (17,33). In the present study, we observed inhibition of autophagy and autotic cell death in hippocampal-CA3-region neurons of rats treated with neriifolin, but the inhibition of autotic cell death in this region of the hippocampus is not sufficient to explain the dramatic reduction in overall ipsilateral infarct size following hypoxia-ischemia.…”
Section: S6csupporting
confidence: 86%
“…Several cell-death morphologies have been identified in different regions of the brain after neonatal hypoxic-ischemic injury, but neuron-specific deletion of Atg7 or intracerebroventricular treatment with the autophagy inhibitor, 3-MA, is sufficient to reduce infarct lesion volume, indicating that autophagy may be upstream of multiple death pathways. This supports our previous recommendation that postischemic treatment of neonatal cerebral hypoxia-ischemia should target autophagy (17,33). In the present study, we observed inhibition of autophagy and autotic cell death in hippocampal-CA3-region neurons of rats treated with neriifolin, but the inhibition of autotic cell death in this region of the hippocampus is not sufficient to explain the dramatic reduction in overall ipsilateral infarct size following hypoxia-ischemia.…”
Section: S6csupporting
confidence: 86%
“…Because inhibition of I Na by TTX reduces hypoxia-induced death in neuronal cultures (Boening et al, 1989;Stys et al, 1992;Weber and Taylor, 1994;Xie et al, 1994;Taylor et al, 1995;Fung et al, 1999;Horn and Waldrop, 2000;Raley-Susman et al, 2001;Banasiak et al, 2004), the response we study here -acute hypoxic recruitment of SUMO to Na V 1.2 channels leading to increased CGN I Na -might be expected to be deleterious. However, neuronal pathology depends on the etiology, severity, and duration of the insult (Puyal et al, 2013). Thus, increased I Na may be self-limiting (or protective) if it leads to membrane depolarization, inducing Na V channel inactivation and, thereby, limits subsequent Na + flux.…”
Section: Discussionmentioning
confidence: 99%
“…lizozomske degradacije. U skladu s tim, dokazano je da obnova funkcije lizozoma u životinjskim modelima Alchajmerove demencije dovodi do obnove neuronske funkcije i poboljšanja kognitivnih funkcija (9). Dakle, modulacija autofagije u određenoj situaciji treba da bude posmatrana ne samo statičnom analizom autofagnih markera nego dinamičkim praćenjem celokupnog procesa autofagije, odnosno autofagnog fluksa.…”
Section: Rezultatiunclassified
“…Poznato je, međutim, da se većina proteina uključenih u biogenezu autofagozoma, osim LC3-II na unutrašnjoj membrani, uklanja pre nego što se završi kompletno formiranje autofagozoma i da se ovi proteini verovatno recikliraju za ponovnu upotrebu (9). Stoga je ovo moguće objašnjenje zašto sinteza novih proteina nije esencijalna za indukciju autofagije i formiranje autofagozoma, kao i zašto pod dejstvom glutamata ne dolazi do potpune inhibicije autofagije nego samo do njenog smanjenja, što pokazuju i rezultati imunoblot analize i fluorescentna mikroskopija.…”
Section: Rezultatiunclassified
See 1 more Smart Citation